Effects of surgically implanted transmitters on reproduction and survival in mallards - Jennifer L. Sheppard; Todd W. Arnold; Courtney L. Amundson; David Klee (Wildlife Society Bulletin)
ABSTRACT Abdominally implanted radiotransmitters have been widely used in studies of waterbird ecology; however, the longer handling times and invasiveness of surgical implantation raise important concerns about animal welfare and potential effects on data quality. Although it is difficult to assess effects of handling and marking wild animals by comparing them with unmarked controls, insights can often be obtained by evaluating variation in handling or marking techniques. Here, we used data from 243 female mallards (Anas platyrhynchos) and mallard–grey duck hybrids (A. platyrhynchos × A. superciliosa) equipped with fully encapsulated abdominally implanted radiotransmitters from 2 study sites in New Zealand during 2014–2015 to assess potential marking effects. We evaluated survival, dispersal, and reproductive effort (e.g., breeding propensity, nest initiation date, clutch size) in response to 3 different attributes of handling duration and procedures: 1) processing time, including presurgery banding, measurements, and blood sampling of unanaesthetized birds; 2) surgery time from initiation to cessation of anesthetic; and 3) total holding time from first capture until release. We found no evidence that female survival, dispersal probability, or reproductive effort were negatively affected by holding, processing, or surgery time and concluded that we collected reliable data without compromising animal welfare. Our results support previous research that techniques using fully encapsulated abdominal‐implant radiotransmitters are suitable to enable researchers to obtain reliable estimates of reproductive performance and survival. © 2017 The Wildlife Society.